(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2019)
The objective of the article is the theoretical analysis of the elaboration of a didactic model of the curricular multigrade integrative dynamics for the teaching-learning process in the multigrade classroom of the rural sector, and its foundation like process that elevates the preparation of the subjects and the teacher of the multigrade classroom not used before in the rural sector by the educational community in the rural areas of the Granma’s province. The model is introduced in the Program and Methodological Orientations of the Didactic subject of the work in the multigrade classroom for the pregrado of the career of Degree in Primary Education of the University of Granma and the postgraduate degree to the professionals that work in the rural areas of the plain and the mountain that it allows to favor the educational and social relevancy for this teaching.